2017
DOI: 10.1097/wnr.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics changes with age in an APPsw/PS1dE9 mouse model of Alzheimer’s disease

Abstract: Increasing research suggests that mitochondrial defects play a major role in Alzheimer’s disease (AD) pathogenesis. We aimed to better understand changes in mitochondria with the development and progression of AD. We compared APPsw/PS1dE9 transgenic mice at 3, 6, 9, and 12 months old as an animal model of AD and age-matched C57BL/6 mice as controls. The learning ability and spatial memory ability of APPsw/PS1dE9 mice showed significant differences compared with controls until 9 and 12 months. Mitochondrial mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…These data confirm that SVCT2 is not preferentially conserved in mitochondria and ASC concentration within mitochondria is primarily determined by expression of the transporter. Aβ peptides can interact with mitochondrial membrane proteins leading to structural and functional alterations, which may then result in inefficient ATP production and an increase in mitochondrial activity [45,55,56]. While there is little amyloid accumulation prior to 6 months in the APP/PSEN1 mouse model [43,57], the Aβ peptide is present and measureable at 4 months in the APP/PSEN1 mouse model, as demonstrated qualitatively by western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data confirm that SVCT2 is not preferentially conserved in mitochondria and ASC concentration within mitochondria is primarily determined by expression of the transporter. Aβ peptides can interact with mitochondrial membrane proteins leading to structural and functional alterations, which may then result in inefficient ATP production and an increase in mitochondrial activity [45,55,56]. While there is little amyloid accumulation prior to 6 months in the APP/PSEN1 mouse model [43,57], the Aβ peptide is present and measureable at 4 months in the APP/PSEN1 mouse model, as demonstrated qualitatively by western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, with disease progression, the level of Mfn2 expression increased compared to wild-type mice. These data suggest that aberrant mitochondrial dynamics may be considered an early event in AD progression [48].…”
Section: Mitochondrial Dysfunction In Alzheimer's Diseasementioning
confidence: 87%
“…Xu et al investigated the expression of mitochondrial proteins with AD progression in APP/PS1 mice and found differences in mitochondrial fusion and fission proteins as compared to age-matched C57BL/6 mice. The results showed a significant increase of fission and fusion protein (Drp1, Fis1, Mfn2) levels in 3 month-old APP/PS1 mice [48]. Interestingly, with disease progression, the level of Mfn2 expression increased compared to wild-type mice.…”
Section: Mitochondrial Dysfunction In Alzheimer's Diseasementioning
confidence: 93%
“…Several papers have shown that both fusion and fission could be altered in AD. Although one paper has suggested that both fusion and fission markers are increased in AD, others report that mitochondrial fusion is decreased but mitochondrial fission is increased in AD, which as in HD and PD causes fragmentation of the mitochondria . It has also been suggested that rather than drp1 causing mitochondrial fragmentation, the OMM receptor Fis1 levels were increased .…”
Section: Mitochondrial Dysfunction In Neurodegenerationmentioning
confidence: 99%